Overall Key Performance Indicator to Optimizing Operation of High-Pressure Homogenizers for a Reliable Quantification of Intracellular Components in Pichia pastoris - Garcia-Ortega, Xavier; Reyes, Cecilia; Montesinos, José Luis; Valero, Francisco (Frontiers in Bioengineering and Biotechnology, 2015)
The most commonly used cell disruption procedures may present lack of reproducibility, which introduces significant errors in the quantification of intracellular components. In this work, an approach consisting in the definition of an overall key performance indicator (KPI) was implemented for a lab scale high-pressure homogenizer (HPH) in order to determine the disruption settings that allow the reliable quantification of a wide sort of intracellular components. This innovative KPI was based on the combination of three independent reporting indicators: decrease of absorbance, release of total protein and release of alkaline phosphatase activity. The yeast Pichia pastoris growing on methanol was selected as model microorganism due to it presents an important widening of the cell wall needing more severe methods and operating conditions than Escherichia coli and Saccharomyces cerivisae. From the outcome of the reporting indicators, the cell disruption efficiency achieved using HPH was about 4-fold higher than other lab standard cell disruption methodologies, such bead milling cell permeabilization. This approach was also applied to a pilot plant scale high-pressure homogenizer validating the methodology in a scale-up of the disruption process. This innovative non-complex approach developed to evaluate the efficacy of a disruption procedure or equipment can be easily applied to optimize the most common disruption processes, in order to reach not only reliable quantification, but also recovery of intracellular components from cell factories of interest.